Change of the vortex lattice symmetry in the vicinity of the macro-to-mesoscopic threshold - Zadorosny, R. [UNESP]; Sardella, Edson [UNESP]; Malvezzi, André Luiz [UNESP]; Lisboa Filho, Paulo Noronha [UNESP]; Ortiz, W. A. (Elsevier B.V., 2012)
In the present work we study the influence of the surface on the vortex structure as a function of the sample size for different temperatures. It is shown that a crossover between a hexagonal lattice, which is characteristic of the macroscopic samples, and a square lattice occurs in the vicinity of a threshold line which delimits the macro and the mesoscopic superconducting regimes, L-c(T). Such study was carried out by computational simulations where we used the time dependent Ginzburg-Landau equations in the discretized form. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: TDGL; Mesoscopic; Macroscopic; Vortex lattice